Perceived injustice and its relation to chronic pain outcome in complex regional pain syndrome and chronic musculoskeletal pain - Baum, Corinna; Rebhorn, Cora; Martinelli, Anne; Heining, Dorothee; Weimert, Sabine; Bücher, Sandra; Steenken, Livia; Steinmetz, Sebastian; Birklein, Frank; Dimova, Violeta (Frontiers in Pain Research, 2025)
ObjectivesClinical observations indicate that patients with complex regional pain syndrome (CRPS) tend to ruminate about their illness. Perceived injustice is a negative cognitive-emotional appraisal regarding the severity of loss associated with blame, unfairness, and pain. We investigated injustice beliefs in CRPS compared with chronic musculoskeletal pain (CMP), where previous evidence indicates clinical relevance for pain-related outcome in this patients’ group. The role of perceived injustice in relation to pain intensity and disability was tested through a mediation model including catastrophizing thoughts of pain.MethodsPatients with CRPS (mean age M = 50.9, SD = 13.8) and CMP (mean age M = 53.9, SD = 8.0 years) were enrolled at two independent specialized outpatient clinics. All patients completed questionnaires on pain intensity, pain disability, and perceived injustice, levels of depression and pain catastrophizing.ResultsCRPS patients displayed higher levels of perceived injustice than the CPM patients. Higher pain intensity in both cohorts was indirectly associated with more feelings and beliefs of injustice through a higher tendency to catastrophize about pain and pain-related information. In contrast, only in the CMP group higher pain-related disability was related to higher catastrophizing, which mediated the effect of perceived injustice.ConclusionsPerceived injustice influences especially pain intensity through pain catastrophizing. This interaction appears to be common for both pain syndromes.